UZBEKISTAN'S WELLNESS TOURISM: OPPORTUNITIES FOR INTERNATIONAL INVESTORS AND PARTNERS - Kudratov Mirjalol Khurshid ugli, (TADQIQOTLAR, 2025)
Abstract Central  Asian  Uzbekistan  presents  growing  potential  as  a  destination  for wellness tourism because of its diverse cultural traditions and magnificent scenery. International  investors  and  partners  can  establish  business  opportunities  in Uzbekistan's wealth sector development by addressing this piece. Through its resources and  ancient  landmarks  plus  state  backing  Uzbekistan  can  transform  into  an international wellness tourism hot spot. The ongoing research unveils the main growth factors alongside strategic advice and market barriers for investment development in this  expanding  segment  of  the  Tourism  industry  (Global  Wellness  Institute,  2023; Uzbekistan Tourism Portal, 2025).